For or from democracy? : the pluralistic independence of political central banks - Leitão Amaro, António (2023)
The global financial crisis heralded profound transformations in the economy and the governance of money and credit. The rise and politicization of central banks challenged the twodecade- old consensus on central bank independence (CBI), requiring the reconstruction of the concept, its normative justification and framework. A new model of pluralistic CBI is proposed in which central banks are independent but also political and democratic. It preserves the essence of independence, the functional and institutional separation and delegation of the discretionary governance of monetary and financial policies to a non-majoritarian institution to protect the integrity of the specialized process. Yet, it debunks the traditional illusions of strict separation, absolute insulation, and narrow and clear delegation to central banks that would be apolitical and decide objectively and merely technical issues. Instead, the separation of powers is balanced and limited, and external influences are prohibited, permitted, or even required, depending on their normative value. Pluralistic CBI focuses on influences from the classic political actors and also from the public, courts, epistemic community, and affected private interests. All these Influencers may be "friends or foes" of the IBC. It constrains those influences to prevent domination or systematic biases (majoritarian or minoritarian) and adds a new Madisonian dimension by mobilizing and structuring a "competition of Influencers" that, through mutual checks and balances, protects independence. Central banks are political because they make substantively political decisions, operate under conditions of public contestation, and are "inside" politics, in a bidirectional relationship with political actors. They are democratic because they are subject to appropriate ex ante and ex post control by Democratic Representatives, they establish new channels of direct and bidirectional relationship with the public, and they help to correct some difficulties of contemporary democracies, namely by equalizing representation. By comparative institutional analysis it is shown that the pluralistic model of CBI is superior to the classical political process and traditional CBI in terms of the core values of modern liberal democracies. It has the comparative advantages of specialized expertise, democratic credentials, and impartiality by mitigating domination or systematic majoritarian or minoritarian biases. Pluralistic CBI is a political technology of non-partisan politics and indirect democracy. It is also superior in terms of policy outcomes. The normative reconstruction generates 18 lessons to improve and broaden the CBI framework, which is designed with 67 protections of institutional, personal, financial, and operational independence by combining defensive barriers and structured competition of Influencers.